The trend of lessepsian fish populations with an emphasis on temperature variations in Iskenderun Bay, the Northeastern Mediterranean. (3rd April 2017) - Mavruk, Sinan; Bengil, Fethi; Yeldan, Hacer; Manasirli, Meltem; Avsar, Dursun
Abstract: The fish assemblages of the Eastern Mediterranean are highly variable owing to the Lessepsian migration. So far, there has been limited discussion about the temporal variation of Lessepsian populations, which may be a key to better understanding the establishment, persistence and spreading dynamics of these species. The objective of this study was, therefore, to develop an understanding of inter‐annual variations of Lessepsian fish populations through investigating the effects of climate conditions. For this purpose, we evaluated the data obtained from the seasonal bottom trawl surveys conducted over the course of 12 years, from 2004 to 2015, at the infra‐littoral zone of Iskenderun Bay. Our results indicated that Lessepsians constituted 27%, 62% and 85% of total teleost fishes in the number of species (LS‐%), biomass (LW‐%) and abundance (LN‐%), respectively. The linear trends showed that the dominance of Lessepsian fishes increased with annual rates of 1.9 ( p < .01, LS‐%), 2.77 ( p < .01, LW‐%) and 1.43% ( p < .05, LN‐%) per year during the study period. In contrast, seasonal trend decomposition based on GAMMs revealed that the true shape of trends was non‐linear. The majority of the new Lessepsians entered the study area after 2009 when warmer conditions prevailed. Those new invaders such as Nemipterus randalli, Pomadasys stridens and Apogon smithi successfully settled in a short time and remarkably altered the composition of fish assemblages after 2010. We found that variations of lessepsian fish assemblages were correlated with the increase of annual minima and average values of sea surface temperature.